Parallel Computational Technologies: 15th International Conference, PCT 2021, Volgograd, Russia, March 30 - April 1, 2021, Revised Selected Papers - Sokolinsky, Leonid; Zymbler, Mikhail (Communications in Computer and Information Science, 2021)
This book constitutes refereed proceedings of the 15th International Conference on Parallel Computational Technologies, PCT 2021, held in March-April 2021. Due to the COVID-19 pandemic the conference was held online.The 22 revised full papers presented were carefully reviewed and selected from 89 submissions. The papers are organized in topical sections on high performance architectures, tools and technologies; parallel numerical algorithms; supercomputer simulation.